The commission and the police - Skogan, Wesley G. (Criminology & public policy, 2018)
The major conclusions advanced in the 1967 report by the U.S. President's Commission on Law Enforcement and Administration of Justice under President Johnson are reviewed in this article. Six of the Commission's visions for law enforcement are described, and subsequent changes in the character of American policing are traced. Many of the concerns of the Commission linger until this day. Progress on many fronts has been halting, their impact more muted than reformers had hoped, and the framework of institutions that define law enforcement in the United States has proved remarkably resistant to change.